(untitled) (Theatrum historiae, 2023)
The paper focuses on the issue of intersexuality in the Czech medical discourse during the first half of the 20th century, when the term “intersex”, which is officially used today and distinct from intersexuality, did not yet exist. Intersexuality can be understood as a universal category within which doctors linked various other issues, such as hermaphroditism, pseudohermaphroditism, and homosexuality. Doctors attempted to label the variability of the human body, but were heavily influenced by their own ideas of the “ideal” male and female body and unable to think beyond these binary categories. In the past, any deviation from the normative was often considered a disease. Dictionaries and medical manuals were used to develop theoretical understandings of these concepts. The study also examines the literary work of the Czech physician Emil Tréval (a.k.a. Walter), who, in his novel Maia, presented the story of a man who was born as a hermaphrodite and struggled with this stigma throughout the plot. The second example refers to a real-life case of a person identified as a man in society, despite being born with a female biological body, referred to by doctors with the initials A.H. The doctors labelled A.H. as homosexual and a transvestite, which we now consider to be incorrect from a modern perspective.